First record of Dasineura gleditchiae (Osten Sacken, 1866) in Belarus - Sinchuk, Aleh V.; Kolbas, Aliaksandr P. (Experimental Biology and Biotechnology, 2019)
The information given on the first record of alien species is honeylocust podgall midge in Belarus. Dasineura gleditchiae (Diptera: Cecidomyiidae) is a pest of Gleditsia triacanthos (Fabaceae) originating from North America. Most likely, the penetration of the species occurred with contaminated planting material.